Turkish-Russian relations in the Syrian region in the context of security since 2016 - Özer, Çağlar (Transnational Press London, 2025)
Relations between Türkiye and Russia have historically been shaped by a balance of competition and cooperation. The interaction between the two countries can be examined from a broad perspective, ranging from the wars between the Ottoman Empire and Tsarist Russia to the ideological rivalry of the Cold War. At times, both nations have formed alliances in line with their geopolitical interests, while at other times, they have engaged in intense competition. With the end of the Cold War in the 1990s, bilateral relations took on a new dimension, particularly in the areas of economic and energy cooperation. Türkiye’s increasing energy demand and Russia’s role as a dominant regional supplier strengthened economic ties between the two countries. However, diplomatic relations have experienced periodic fluctuations, largely shaped by the regional security policies of both nations. While Türkiye’s NATO membership and its strategic partnership with the West have occasionally created tensions with Russia, economic and energy cooperation has remained a stabilizing factor in bilateral relations. However, the Syrian crisis, which erupted in 2011, has put Turkish-Russian relations to a new test. While Türkiye adopted an active foreign policy in Syria to ensure border security and manage the flow of Syrian migrants, Russia pursued a strategy of ensuring the continuation of the Assad regime by increasing its military presence in the region. These different priorities led to diplomatic tensions, such as the plane crisis in 2015, but in the post-2016 period, cooperation processes between the parties came into effect. Türkiye’s security concerns in Syria are based on three main factors: border security, counterterrorism and the migrant crisis. These factors have been the main factors shaping Türkiye’s military interventions and presence in the region.
Keywords: Turkey–Russia relations; Syrian conflict; Security policy; Regional geopolitics; NATO